MSMEs Performance in Nigeria: A Review of Supply Chain Collaboration Challenges - Okon, Emmanuel O. (International Journal of Marketing Research Innovation, 2018)
MSMEs are seen as a veritable engines of economic development, but the growth and development of small and medium scale enterprises in Nigeria have been slow and in some cases even stunted, due to a number of problems and challenges confronting this all-important sub-sector of the economy. Facing uncertain environments, firms have strived to achieve greater supply chain collaboration to leverage the resources and knowledge of their suppliers and customers. However, there are many challenges that affect the MSMEs supply chain collaboration worldwide though some are prevalent in developing world. Based on relevant literature, this paper reviewed the supply chain collaboration challenges affecting MSMEsdevelopment and performance in Nigeria. Conclusion and suggestion were offered as well.